New Technologies Impact in Nowadays Shopping Centers Marketing - Ioniţă (Moldoveanu), Irene Mihaela (International Journal of Economic Practices and Theories, 2014)
Shopping centers are an important aspect of the extremely dynamic life of the 21st century consumer. Nowadays, worldwide, shopping centers represent significant investments, remarking themselves with bold architectures and structures and an individual brand image. Retail markets are currently under transformation by a confluence of new retailing technologies, dramatic shifts in the demographic profile and preferences of more affluent and educated shoppers. Still in process of recovering from the devastating recession, retailers and landlords are facing a new set of challenges as Internet technology is transforming both consumer behavior and retailing business models. E-commerce2 is upending traditional retailing strategies by greatly expanding shopping convenience, selection and affordability. Computers and mobile devices will mix the virtual and real shopping experiences and will affect how shopping centers are planned and managed, better accommodating the needs of individual shoppers to an “E”-model.